Extracellular vesicles derived from macrophages display glycyl‐tRNA synthetase 1 and exhibit anti‐cancer activity. Issue 1 (1st December 2020) - Goughnour, Peter C.; Park, Min Chul; Kim, Sang Bum; Jun, Sangmi; Yang, Won Suk; Chae, Sehyun; Cho, Seongmin; Song, Chihong; Lee, Ji‐Hyun; Hyun, Jae Kyung; Kim, Byung Gyu; Hwang, Daehee; et al.
Abstract: Glycyl‐tRNA synthetase 1 (GARS1), a cytosolic enzyme secreted from macrophages, promotes apoptosis in cancer cells. However, the mechanism underlying GARS1 secretion has not been elucidated. Here, we report that GARS1 is secreted through unique extracellular vesicles (EVs) with a hydrodynamic diameter of 20–58 nm (mean diameter: 36.9 nm) and a buoyant density of 1.13–1.17 g/ml. GARS1 was anchored to the surface of these EVs through palmitoylated C390 residue. Proteomic analysis identified 164 proteins that were uniquely enriched in the GARS1‐containing EVs (GARS1‐EVs). Among the identified factors, insulin‐like growth factor II receptor, and vimentin also contributed to the anti‐cancer activity of GARS1‐EVs. This study identified the unique secretory vesicles containing GARS1 and various intracellular factors that are involved in the immunological defence response against tumorigenesis.